Oral Health Disparities in Children of Immigrants: Dental Caries Experience at Enrollment and during Follow-Up in the New England Children’s Amalgam Trial - Nancy Nairi Maserejian, ScD; Felicia Trachtenberg, PhD; Catherine Hayes, DMD, SM, DrMedSc; (Blackwell Synergy, 2008)
Previous research shows increased dental decay among immigrants, but little is known about the oral health of the growing population of children of immigrants.